Shelf Life Study of Seasoning Using Accelerated Shelf Life Testing (ASLT) Method Based on Critical Moisture Content Approach - Budijanto, Slamet; Sitanggang, Azis Boing; Silalahi, Beti Elizabeth; Murdiati, Wita (Jurnal Teknologi Pertanian, 2010)
There were six kinds of seasoning analyzed in this study. Two kinds from beef flavor, two kinds from chesee flavor, one kind from corn flavor, and one kind from chicken flavor. Shelf life determination employed ASLT method based on critical moisture content approach. Using modification of Labuzaâ€™s equation in two different temperature values (25oC, 38oC, RH 70%) and in respect of packaging information (k/x, A, âˆ†P), the shelf lives of those seasonings were morethan one year. Precisely, the shelf lives of the seasonings with the storage conditions of 70% of RH and 25ï‚°C was between 2429 days up to 4730 days. Whereas the shelf lives of the seasonings in the same relative humidity value and at 38oC was between 1161 days up to 2261 days. Application of high storage temperature was proven to shorten the shelf life stability of those seasonings.Keywords: shelf life, seasoning, Accelerated Shelf Life Testing (ASLT), Labuza